First Evidence of Interference effects in the ionization of N2 molecule. (August 2015) - Ozer, Zehra N; Chaluvadi, Hari; Dogan, Mevlut; Colgan, James; Madison, Don
Synopsis: We will present an experimental and theoretical investigation of triple differential cross sections for electron- impact ionization of nitrogen molecules at intermediate energies. A discussion of interference effects contained in the theoretical and experimental interference factors will be presented.